CREATIVE WORK AS A METHOD OF CORRECTION OF THE PSYCHOEMOTIONAL STATE IN PUPILS OF HIGH SCHOOL (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
A preliminary report is given on the comparative study of the level of psycho-emotional state of students studying at the “Quant” gymnasium and the State College of Fine Arts in different educational environments. The comparative analysis of the obtained data shows that creative work has a relaxing effect on mental tension, allows the individual to better adapt to life, allows for self-knowledge.
Keywords: extravert; introvert; Eysenck questionnaire; gymnasium; college